Remote Viewing the Future with a Tasking Temporal Outbounder - Brown, Courtney (Journal of Scientific Exploration, 2012)
This study uses remote viewing in a predictive manner within the context of a novel experimental design to describe eleven target events spread out over a year, each of which occurs approximately one month after the remote-viewing sessions are completed. The study was conducted at The Farsight Institute using 12 highly experienced remote viewers who were trained in the use of four remote-viewing methodologies that are the same as or derived from those previously used by the United States military for espionage purposes. While prediction using remote viewing has a long and spotted history, the current investigation is aimed at enhancing our understanding of the remote-viewing phenomenon by utilizing a temporal outbounder approach to tasking in order to improve the description of future events. In this design, the tasker is located in time after the remote-viewing sessions are completed and after the occurrence of the chosen target event. Exploiting one of the largest bodies of remote-viewing data ever collected using military-related viewing methodologies, this study finds strong support for hypothesis that experimental designs utilizing a temporal outbounder as a tasker greatly enhances the accuracy of remote-viewing descriptions of future events. The causal mechanism for why this might occur is left to be determined by future research.